DIRECTIONS FOR DEVELOPING THE FINANCIAL STABILITY OF AGRICULTURAL CLUSTERS - Yuldasheva Dildora Kamiljan qizi (Modern American Journals, 2025)
Agricultural clusters have emerged as a vital mechanism for strengthening rural economies, enhancing competitiveness, and ensuring food security. Despite these advantages, clusters often struggle with financial instability due to seasonal revenue flows, limited access to finance, climate risks, and global price volatility. This study investigates the financial challenges of agricultural clusters and proposes strategic directions for developing financial stability. A mixed-method approach was applied, combining literature review, comparative case studies of Uzbekistan, Poland, and Turkey, stakeholder interviews, and SWOT analysis. The findings highlight five key strategic directions: diversification of financial sources, development of risk management mechanisms, strengthening internal financial management, adoption of digital financial technologies, and enhanced government support. The study concludes that financial resilience requires a multi-level strategy, integrating institutional, technological, and policy dimensions. These recommendations provide a practical roadmap for policymakers, cluster managers, and financial institutions to improve the financial sustainability of agricultural clusters.
Keywords: Agricultural clusters, financial stability, risk management, digital finance, food security, sustainable development